(untitled) (Research, Society and Development, 2024)
In primary health care, the nurse, who is part of the multidisciplinary team, can carry out actions aimed at preventing Gestational Diabetes Mellitus (GDM) and its problems. In this context, the objective is to understand the role of nurses in the prevention and treatment of GDM during prenatal consultations. This study consists of an integrative review of the literature, conducted in the Nursing Databases (BDENF), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), with a search for publications between 2019 and 2024. In total, 26 publications were identified, the results of which demonstrate that the nurse is responsible for identifying and monitoring pregnant women who have the possibility of developing GDM, as well as supporting pregnant women diagnosed with this metabolic condition. Research highlights the benefits of this action in preventing complications, both for the mother and the fetus, through assistance and educational measures, contributing to a peaceful and healthy pregnancy. The nurse tracks pregnant women at risk by assessing risk factors, symptoms, and glucose tests; while diagnosed pregnant women receive guidance on blood glucose tests during pregnancy, in addition to support for drug therapy and physical activity, when indicated, there is also individualized nutritional guidance, considered essential to achieving the expected results during pregnancy.